Real-time audio-visual composition: Mugenkei as a Live Dream. (26th March 2009) - Jentzsch, Wilfried; Detheux, Jean
As the finale of the DigArt Symposium, Jean Detheux (images) and myself (music) have presented the performance Mugenkei as a Live Dream. This consisted of an improvised visual music where images and music have been produced in real-time. This article will review the performance from the viewpoint of the relationship between images and music.